The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2494.2007.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect on upland beef production of incorporating winter feeding of red clover silage or summer grazing of Molinia‐dominated semi‐natural pastures

Abstract: Fraser, M. D., Davies, D. A., Wright, I. A., Vale, J. E., Nute, G. R., Hallett, K. G., Richardson, R. I. (2007). Effect on upland beef production of incorporating winter feeding of red clover or summer grazing of Molinia-dominated semi-natural pastures. Grass and Forage Science, 62 (3), 284-300 Sponsorship: UK Department for Environment, Food and Rural Affairs, the Scottish Executive Environment and Rural Affairs Department and the Meat and Livestock Commission.Management systems for finishing beef cattle, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Livestock production systems in these countries rely heavily on C 3 temperate grasslands (Evans & Gaskell, 2003;Fraser, 2007). The same is also true for the other European countries (Conner, Hamilton, Sheeby, Stuth, & Kreuter, 1998) considered in this study (Fig.…”
Section: How Does the Global Distribution Of C 3 And C 4 Plants Impacmentioning
confidence: 59%
“…Livestock production systems in these countries rely heavily on C 3 temperate grasslands (Evans & Gaskell, 2003;Fraser, 2007). The same is also true for the other European countries (Conner, Hamilton, Sheeby, Stuth, & Kreuter, 1998) considered in this study (Fig.…”
Section: How Does the Global Distribution Of C 3 And C 4 Plants Impacmentioning
confidence: 59%
“…There is increasing interest in cattle production from botanically diverse pastures but there is a paucity of information on the fatty acid composition of beef produced from such pastures. Fraser et al (2007) reported that inclusion of a period of grazing a Molinia caerulea (purple moor grass) dominated semi-natural pasture increased the proportion of n − 3 PUFA in muscle lipids. A review by Moloney et al (2008) considered studies that compared grazing of a ryegrass pasture with unimproved saltmarsh pasture (Whittington, Dunn, Nute, Richardson, & Wood, 2006), grazing of Table 1 Effect of forage type, oil supplementation and ruminally protected lipid supplements on the total fatty acids (mg/100 g muscle) and the fatty acid composition of beef muscle (g/kg fatty acids).…”
Section: Forages and The Fatty Acid Composition Of Beefmentioning
confidence: 99%
“…Incorporating red clover silage into the winter diet of an upland beef system increased live-weight gain relative to animals offered low feed value grass silage (DOMD 586 g kg -1 ) (Fraser et al 2007). In the same study, meat from the steers fed on red clover silage over winter had a higher lipid oxidation than steers grazing permanent pasture supplemented with grass silage (previously ensiled from that pasture) probably related to the vitamin E content of the loin muscle, however there were no differences between treatments in the sensory properties (texture, juiciness or flavor) of the beef.…”
Section: Red Clover and Lucernementioning
confidence: 99%